2023
DOI: 10.3390/microorganisms11081954
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing-Based Screening of MRSA in Patients and Healthcare Workers in Public Hospitals in Benin

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) constitutes a serious public health concern, with a considerable impact on patients’ health, and substantial healthcare costs. In this study, patients and healthcare workers (HCWs) from six public hospitals in Benin were screened for MRSA. Strains were identified as MRSA using conventional microbiological methods in Benin, and confirmed using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry in Belgium. Whole-genome sequencing (WGS) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…It is also noteworthy that the WGS-based prediction of AMR based on ARG presence was largely consistent with phenotypic AST results, underscoring the potential of WGS in predicting AMR accurately. Whole genome sequencing has been used by several studies to assess the potential for predicting AMR genes from genomes of pathogens and validating concordances with the phenotypic results [ 19 55 56 ]. In our study, we used five AMR databases to predict AMR genes to prevent the chance of missing any AMR acquired genes or chromosomal point mutation in the genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also noteworthy that the WGS-based prediction of AMR based on ARG presence was largely consistent with phenotypic AST results, underscoring the potential of WGS in predicting AMR accurately. Whole genome sequencing has been used by several studies to assess the potential for predicting AMR genes from genomes of pathogens and validating concordances with the phenotypic results [ 19 55 56 ]. In our study, we used five AMR databases to predict AMR genes to prevent the chance of missing any AMR acquired genes or chromosomal point mutation in the genes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, WGS predicted presence of fosB , a fosfomycin resistance gene and point mutations in genes contributing resistance to fosfomycin. We did not perform any phenotypic tests for fosfomycin resistance, however previous studies have used WGS and identified fosB and similar point mutation in S. aureus belonging to ST8, ST5, ST30 [ 56 58 ]. The fosB or related point mutations were not identified in CC97 isolates in our study which agrees with findings from another study [ 58 ].…”
Section: Discussionmentioning
confidence: 99%